Addressing disparities in Pre-exposure Prophylaxis (PrEP) access: implementing a community-centered mobile PrEP program in South Florida - Stefani A. Butts; BreAnne Young; Jakisha Blackmon; Susanne Doblecki-Lewis (BMC, 2023)
Abstract Background Pre-exposure prophylaxis (PrEP) for HIV prevention is highly effective, but disparities in PrEP access remain considerable, particularly among Black and Latino men who have sex with men (MSM). To address this, the University of Miami Mobile PrEP Program was created, offering mobile HIV prevention/PrEP services in areas throughout South Florida where HIV incidence is high and PrEP access is geographically limited. Using a community-centered participatory approach, the program strategized and executed expansion into the Liberty City neighborhood of Miami. This study qualitatively assessed factors affecting Mobile PrEP implementation as perceived by community stakeholders, clients, and program staff. Methods Forty-one in-depth interviews were conducted with 21 Mobile PrEP clients, 10 key informants from local health organizations, and 10 program staff. Interview questions queried perceived organizational and positional barriers and facilitators to mobile clinic implementation. Service satisfaction, setting preferences, social factors, and likelihood of recommending Mobile PrEP were also assessed. A thematic content analysis was performed using the Consolidated Framework for Implementation Research (CFIR) taxonomy as the guiding constructs for the analysis. Results Participant statements indicated that providing no-cost services, convenient location, program-covered rideshares, individualized patient navigation, and a community-centric approach to patient care, which included staff members with shared lived experiences to increase positive interactions and renewed trust among poorly served communities, were facilitators of PrEP access and intervention uptake. The importance of program familiarization with the community before implementation, particularly for Black and African American communities, who may experience unique barriers to accessing sexual healthcare was strongly emphasized by participants. Conclusions The Mobile PrEP intervention was found to be an acceptable and accessible mode of HIV/STI preventive care. The importance of pre-implementation community engagement and preparation is emphasized. Future research is needed to refine understanding of the intervention's components and evaluate implementation determinants in other highly impacted neighborhoods.